Pressure control strategies in biosafety level-3 large-scale production facilities for animal vaccines - Lei Liang; Xin Feng; Yi Li (Elsevier, 2020)
This paper summarized the pressure control methods used in 16 large-scale production facilities in China for vaccines against foot-and-mouth disease virus and highly pathogenic avian influenza virus. We presented the pressure control modes, with their characteristics, of the "constant supply" mode - variable exhaust air volume system and the "constant supply" mode - constant exhaust air volume system. This paper analyzed the influence of common problems (e.g., pressure reference zero drift, positive pressure reversal and failure to restore the original normal working conditions after working condition conversion) on system stability during pressure control in BSL-3 large-scale production facilities and their solutions, providing references for the design and implementation of similar construction projects under the new situation.